(3eGdGjSY GdWHjH Lgdgs - (3jhSa Hf ESeGYjd Hf EdjGS Hf CMeO, CHh GdeMGSf, fUjQ GdOjf GdNhjj GdTGaYqj GdHZOGOj GdeYQha HGHf GdcJHj,J (B754 (3g` s ((3ESeGYjd Hf EHQGgje GdeJHhdj GdebQi GdTGaYi s)
(3ChdgG (B:s
(3hHYO aEfg deG cGf GdEfSGf Hd GdMjhGf Ef LedI ef GdeQcHGJ GdYfUQjI , hGdeJhGdOGJ GdEeJRGLjI, EbVi Gf jchf OGFekG BNPkG ai GdPHhd hGdJMdd eJbdH GdCMhGd ef GdJZjQ Edi GdJPHd s
(3BNQgG (B:s
(3Heg(B: (3GSe HGdeZQH dfHJg hQbgG jTHg hQb GdgfOHG EdG CfgG CUZQ heGSGb jNQL ef hSWgG hgj oeLQHg aj EdUGb GdLQMGJ WQjI hjGHSI hGddg CYde Je gPG GdcJGH s
(3GfXQ agQS GdWH HQbe (B216s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B144s
Keywords: (3GdWHs